?STABILITY OF RUST RESISTANCE AND YIELD POTENTIAL OF SOME ICARDA BREAD WHEAT LINES IN PAKISTAN (Biological Sciences - PJSIR, 2003)
Thirty bread wheat lines resistant to Yellow rust (Yr) were selected after careful screening from two ICARDA nurseries during 1998 - 1999, Rabi season at Nuclear Institute for Food and Agriculture (NIFA), Tarnab, Peshawar under severe disease pressure. In the following crop cycle, these selections were again field evaluated for stability and effectiveness of Yr resistance at multilocations while their yield potential was ascertained at Tarnab in two different trials with Tatara as commercial check. Results revealed that uniformity was found in the potential behavior of 23 lines (77%) in both the cropping seasons against Yr. This included some high yielding (up to 7067 kg / ha) and low yielding lines (up to 4333 kg / ha) when compared with the check (6089 kg / ha). Yield potential of some high yielding lines with stable Yr resistance should be further evaluated over sites and seasons for wide adaptability, under national uniform testing in order to select and deploy future varieties to combat Yr for acquiring food security in Pakistan.